A Case of Hemophagocytic Lymphohistiocytosis Secondary to Disseminated Histoplasmosis. (20th August 2020) - Columbus-Morales, Ivan; Maahs, Lucas; Husain, Sanam; Gordon, Stuart C.; Inamdar, Kedar V.; Gonzalez, Humberto C.
Abstract : Hemophagocytic lymphohistiocytosis (HLH) is a rare condition characterized by a pathologic immune dysregulation resulting in extreme inflammation. Clinical manifestations are varied but can include severe multiorgan failure and death. HLH has been associated with malignancies, autoimmune diseases, and infections, such as histoplasmosis. Histoplasmosis commonly has subclinical manifestations but can also present in its disseminated form. We present the case of an immunocompromised patient with worsening liver function caused by hepatic histoplasmosis that later triggered HLH with severe multiorgan dysfunction.